2012
DOI: 10.1021/jp305876r
|View full text |Cite
|
Sign up to set email alerts
|

First Principles pKa Calculations on Carboxylic Acids Using the SMD Solvation Model: Effect of Thermodynamic Cycle, Model Chemistry, and Explicit Solvent Molecules

Abstract: Aqueous pK(a) values are calculated from first principles for a set of carboxylic acids using the SMD solvation model with various model chemistries, thermodynamic cycles, and treatments of explicit solvation. In all, 108 unique theoretical protocols are examined. The direct (D) and water proton exchange (PX) cycles are trialled along with a new approach, termed the semidirect (SD) cycle. The SD thermodynamic cycle offers some improvements over the D and PX schemes, as it bypasses the gas-phase heterolytic bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…In Sutton et al, [14] it was shown that, using the M05-2X/cc-pVTZ level of theory with the SMD solvent model [15] for modeling the vibrational wavenumbers of free carboxylate anions in aqueous solution, am ean unsigned error of 4cm À 1 for n a and 28 cm À1 for n s was obtained. This model chemistry was originally proposed for modeling carboxylic acids in Sutton et al, [16] by determining the most accurate methods to calculate the pK a .T his model chemistry is utilized in this investigation. All calculations are performed using Gaussian 09.…”
Section: Methodsmentioning
confidence: 99%
“…In Sutton et al, [14] it was shown that, using the M05-2X/cc-pVTZ level of theory with the SMD solvent model [15] for modeling the vibrational wavenumbers of free carboxylate anions in aqueous solution, am ean unsigned error of 4cm À 1 for n a and 28 cm À1 for n s was obtained. This model chemistry was originally proposed for modeling carboxylic acids in Sutton et al, [16] by determining the most accurate methods to calculate the pK a .T his model chemistry is utilized in this investigation. All calculations are performed using Gaussian 09.…”
Section: Methodsmentioning
confidence: 99%
“…For the description of the solvent effect in the condensed phase, both in the ground and excited states, the SMD 45 solvation model of Truhlar and co-workers were employed (in the following referred to as implicit model or Imp for short), which is based on the conductor polarized continuum model (CPCM). 46,47 According to previous studies, the PCM approaches satisfactorily describe the electrostatic effect of water molecules on solutes similar to C102 48 , while the SMD method is widely used for systems dominated by non-electrostatic interactions 49 and frequently applied to the calculation of ground-state pK a -s. 50 Two approaches of the CPCM solvation model were employed: 51 the equilibrium (eq) and the non-equilibrium (non-eq) solvation, which take into account if the solvent molecules have enough time to reorient according to the electron density of the solute. In addition to the implicit approaches the specific solvent interactions in the aqueous solution were also modeled by adding an explicit water molecule (implicit-explicit or For the simulation of the experimental absorption spectra vertical excitation energies and oscillator strengths were computed at the optimized ground-state geometries.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Accordingly, many researchers are tending to calculation of pKa values using theoretical and computational approaches. 21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Recently quantum chemical calculations, using thermodynamical parameters such as Gibbs free energy, have reported good correlations between calculated and experimental acidities of a wide range of organic and inorganic acids. 18,[42][43][44][45][46][47][48][49][50] For example, gas phase and solution phase acidities of some organic compounds investigated by Namazian et al and Kheirjou et al reported good correlation between ab initio calculations of pKa values with the experimental data.…”
Section: Introductionmentioning
confidence: 99%